Effect of Sorbent Weight on H2S removal by Biochar and Hydrogel Biochar derived from Rice Husk - Bahari Alias, Azil; Ariff Amir Hamzah, Muhamad; Abdul Rashid, Zulkifli; Rahman Mohd Nor, Amirul; Azlina Wan Ab Karim Ghani, Wan (International Journal of Engineering and Technology, 2018)
Biochar has received great attention recently as it has the potential to be alternative absorbent beside the long existence, activated carbon. In this study, biochar was produced from rice husk by slow pyrolysis at temperature of 450Â°C. To increase the performance of the biochar in absorbing H2S, hydrogel biochar was produced by performing polymerization. The characteristics analysis in elemental analysis, functional group, surface area, pore volume and pore size had been done on rice husk, biochar and hydrogel biochar. Then, the absorption of H2S with sorbent weight as parameter has been performed on biochar and hydrogel biochar. The result of H2S absorption by biochar showed that the mass of H2S per weight of sorbent increase as the sorbent weight increase. However, the hydrogel biochar unable to perform the result that has been predicted.Â Â